Answer:
x = 1
Step-by-step explanation:
8 -(x+5) = 5x - 3
-(x+5) ---> -1 (x +5) = -x - 5
8 - x - 5 = 5x -3 8 - 5 = 3
-x + 3 = 5x - 3
+x +x
3 = 6x - 3
+3 +3
6 = 6x
/6 /6
<u>x = 1</u>
Answer: B
Step-by-step explanation:
Answer:
simplified = 8x - 8
Step-by-step explanation:
trust me :)
Answer: 7
Step-by-step explanation:
Answer:
80
Step-by-step explanation:
The Two-Tangent Theorem states that if two tangent segments are drawn to one circle from the same external point, then they are congruent
13+13+9+9+12+12+6+6= 80